PENGARUH MEDIA LATIHAN FOCUS LIGHT TERHADAP AGILITAS DRIBBLING PADA PEMBINAAN BOLA BASKET PENJAS UNTAN - Suryawan, Septi; Simanjuntak, Victor; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to examine the influence of focus light training media on dribbling agility abilities, especially on basketball sports training in the FKIP UNTAN Physical Education Study Program. This research was carried out on the basketball FKIP UNTAN.This type of research is quantitative research with experimental methods in the form of one group pre-test post-test design, where in this design there is a pre-test, before being given treatment so the results of treatment can be known more accurately. The subjects of the trial in this study were members of the basketball training program Physical Education Study Program FKIP UNTAN.The results of the research conducted by researchers can be concluded that the dribbling agility pre-test data of members of the basketball training program FKIP UNTAN Physical Education Study Program is 166.38 seconds. After that the treatment was applied using focus light assistive media and a re-test (post-test). The data obtained in the post-test increased by 41.29 seconds. It can be concluded that the focus light training aid media affect basketball dribbling agility abilities.Â Keywords: Exercise Media, Basketball, Dribbling Agility